Acidity‐Activatable Nanoparticles with Glucose Oxidase‐Enhanced Photoacoustic Imaging and Photothermal Effect, and Macrophage‐Related Immunomodulation for Synergistic Treatment of Biofilm Infection. Issue 46 (10th October 2022) - Dai, Yong; Mei, Jiawei; Li, Zhe; Kong, Lingtong; Zhu, Wanbo; Li, Qianming; Wu, Kerong; Huang, Yan; Shang, Xifu; Zhu, Chen
Abstract: The pH‐responsive theragnostics exhibit great potential for precision diagnosis and treatment of diseases. Herein, acidity‐activatable nanoparticles of GB@P based on glucose oxidase (GO) and polyaniline are developed for treatment of biofilm infection. Catalyzed by GO, GB@P triggers the conversion of glucose into gluconic acid and hydrogen peroxide (H2 O2 ), enabling an acidic microenvironment‐activated simultaneously enhanced photothermal (PT) effect/amplified photoacoustic imaging (PAI). The synergistic effects of the enhanced PT efficacy of GB@P and H2 O2 accelerate biofilm eradication because the penetration of H2 O2 into biofilm improves the bacterial sensitivity to heat, and the enhanced PT effect destroys the expressions of extracellular DNA and genomic DNA, resulting in biofilm destruction and bacterial death. Importantly, GB@P facilitates the polarization of proinflammatory M1 macrophages that initiates macrophage‐related immunity, which enhances the phagocytosis of macrophages and secretion of proinflammatory cytokines, leading to a sustained bactericidal effect and biofilm eradication by the innate immunomodulatory effect. Accordingly, the nanoplatform of GB@P exhibits the synergistic effects on the biofilm eradication and bacterial residuals clearance through a combination of the enhanced PT effect with immunomodulation. This study provides a promising nanoplatform with enhanced PT efficacy and amplified PAI for diagnosis and treatment of biofilm infection. Abstract : Acidity‐activatable nanoparticles of GB@P based on glucose oxidase (GO) and polyaniline (PANI) are developed for the treatment of biofilm infection. The nanoplatform of GB@P exhibits the synergistic effects on the biofilm eradication and bacterial residuals clearance through a combination of the enhanced photothermal effect with immunomodulation.